2015
DOI: 10.1002/2015jc010950
|View full text |Cite
|
Sign up to set email alerts
|

Main eddy vertical structures observed in the four major Eastern Boundary Upwelling Systems

Abstract: In the four major Eastern Boundary Upwelling Systems (EBUS), mesoscale eddies are known to modulate the biological productivity and transport near‐coastal seawater properties toward the offshore ocean, however little is known about their main characteristics and vertical structure. This study combines 10 years of satellite‐altimetry data and Argo float profiles of temperature and salinity, and our main goals are (i) to describe the main surface characteristics of long‐lived eddies formed in each EBUS and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
204
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(245 citation statements)
references
References 116 publications
24
204
1
Order By: Relevance
“…Excluding the mooring-based pro- files, from which we only extracted eddy events, around ∼ 29 % of all profiles (Argo float and shipboard CTD profiles) were taken coincidentally inside of an eddy. This proportion is in the range of earlier results derived by Chaigneau et al (2011), who estimated that ∼ 23 % of their Argo float profiles in the eastern upwelling regions of the Pacific Ocean are conducted in eddies and Pegliasco et al (2015), who found 38 % of all their Argo float profiles in the eastern upwelling areas conducted in eddies. We could also confirm with the result of Pegliasco et al (2015) that the majority of all Argo float profile in eddies are conducted in long-lived anticyclones/ACMEs.…”
Section: Determining the Vertical Structure Of Eddies Detected In Slasupporting
confidence: 74%
“…Excluding the mooring-based pro- files, from which we only extracted eddy events, around ∼ 29 % of all profiles (Argo float and shipboard CTD profiles) were taken coincidentally inside of an eddy. This proportion is in the range of earlier results derived by Chaigneau et al (2011), who estimated that ∼ 23 % of their Argo float profiles in the eastern upwelling regions of the Pacific Ocean are conducted in eddies and Pegliasco et al (2015), who found 38 % of all their Argo float profiles in the eastern upwelling areas conducted in eddies. We could also confirm with the result of Pegliasco et al (2015) that the majority of all Argo float profile in eddies are conducted in long-lived anticyclones/ACMEs.…”
Section: Determining the Vertical Structure Of Eddies Detected In Slasupporting
confidence: 74%
“…This is further discussed below. of upwelling, than in anticyclonic eddies, which are mesoscale downwelling centers (Pegliasco et al, 2015). Many more eddies were present during the June cruises compared to those in August, reflecting the seasonal nature of upwelling.…”
Section: Interspecies Correlationsmentioning
confidence: 94%
“…There is also a particular type of anticyclonic eddy, called intrathermocline (ITE) or subsurface mode water eddy, which represents 30-55% of the anticyclonic eddy population in Eastern Boundary Current Systems (EBCS) [13]. These eddies (ITEs) are characterized by a typical radius of~20-60 km and have a vertical extent of~500 m, together with dome-shaped isopleths in the upper layers and a bowl shape in the lower layers, a minimum in oxygen, and high rates of phytoplankton productivity [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%